A theoretical review on the role of positive emotional classroom rapport in preventing EFL students’ shame: A control-value theory perspective - Kang, Chunxiao; Wu, Jianxiao (Frontiers in Psychology, 2022)
Second/foreign language teaching has been considered as a dialogic and interactive job in which teachers’ and students’ emotions and behaviors are closely connected to each other. When there is a harmonious and positive relationship between the teacher and students in the classroom, many favorable academic outcomes may emerge. A bulk of research has endorsed the power of positive emotional classroom rapport in EFL contexts. However, its role in preventing negative students’ emotions like shame, as an achievement emotion, in terms of perceived control and value tasks has rarely (if any) caught scholarly attention. To fill this gap and provide promising insights into this strand of research, this article systematically reviewed the theoretical and empirical underpinnings of EFL teachers’ positive emotional classroom rapport and students’ shame in light of the control-value theory. Moreover, it drew on previous studies and made recommendations for EFL teachers and practitioners to use some strategies to build a positive emotional classroom rapport as a blocker of students’ shame. Finally, the study presented a number of practical implications for EFL teachers, trainers, principals, and researchers via transmission of emotional mechanisms like emotional contagion, enriching their knowledge of interpersonal aspects of EFL education, and the interplay of several psycho-emotional factors in L2 classes.